NEW NORMAL PARIWISATA YOGYAKARTA - Wicaksono, Ajie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
The Covid-19 pandemic has a major impact on the tourism sector in DIY which causes material losses to Regional Original Income (PAD). This study aims to describe changes in the tourism sector in the conditions before the pandemic, during the pandemic, and the new normal. The results showed that the tourism sector during the pandemic and the new normal era must implement (1) health protocols for the tourism industry such as hotels, restaurants, tourist destinations, and transportation for both visitors and employees by paying attention to cleanliness, health and safety (cleanliness, health, and safety) by providing hygiene facilities such as hand washing and soap, hand sanitizers, and temperature checks with a thermo gun. The hotel even provides isolation rooms for visitors with corona symptoms, (2) Payment using electronic money (cashless). (3) Limiting the number of visitors to prevent crowds and provide a safe distance to minimize spread, and (4) Tourist locations are opened gradually by prioritizing low-risk areas such as natural and mountainous areas. Keywords: Tourism, Covid-19, New Normal, Health Protocol